GAMIFICATION OF MEDICAL PROCESSES - Adilkhan, Sh.; Alimanova, Madina (Journal of Emerging Technologies and Computing, 2020)
Nowadays, almost all areas of activity are switching to digital format. Medicine is no exception. Treatment is often not the most pleasant process, but it is certainly necessary. In medicine, the use of VR technologies is very popular. They help patients get distracted and immerse themselves in a world where they restore their health during the game. Treatment in the form of games is often more effective than traditional treatment. In this article, we have studied the methods of gamification of rehabilitation after certain diseases. Also, we developed a game prototype for the rehabilitation of hands using Leap Motion technology. Modern games are becoming more and more perfect interms of game mechanics and content, which makes it possible to use them not only in the gaming industry, but also in the field of medicine.